Ruins of Aarhus: places that long for time - Ferreira de Souza, Rafael; Pinheiro, Ethel; Albertsen, Niels (Revista de Arquitectura, 2025)
This article proposes a phenomenological approach to the urban exploration of the ruined architectures in the city of Aarhus, Denmark, intending to explore the layer of time in the interpretation of architectures that once formed a material body, but which now face the uncertainty of their meaning for cities. This research seeks to present means for the reconstruction of the imaginary sphere of abandoned urban spaces through the interaction of bodily experience and photography. To achieve this, the research moves through methodologies based on visual anthropology and phenomenological models of multisensory apprehension, finally revealing intersubjective aspects of the material and immaterial elements of the environment that make up some ruined architectures of the city of Aarhus that create places of experience.